UPAYA MASYRAKAT DESA TERHADAP ANAK-ANAK YANG TERPAPAR MEDIA SOSIAL - Sa’diah, Haliza Nur; Kustiawan, Winda; Rambe, Nurul Adila; Dino, Reno Al (Bayan lin-Naas : Jurnal Dakwah Islam, 2025)
This study explores how the community of Sidorejo Village responds to early childhood social media addiction. The research is motivated by the increasing use of platforms such as TikTok and YouTube, which can impact children’s cognitive, emotional, and social development. Using a qualitative approach with a descriptive design, data were collected through interviews and participatory observation involving parents, educators, and community leaders. Findings indicate that parents take active steps to limit screen time, foster positive communication, and model responsible digital behavior. Children also face internal conflict between their desire to use social media and the boundaries set by adults. The study concludes that collaboration among families, schools, and the local community, along with early digital literacy education, is crucial.